The Relationship Between Gadget Use Intensity and Parent–Adolescent Attachment Among Students at Senior High School X - Reynaldi Febriansyah; Dessy Pramudiani; Nurul Hafizah (Journal of Social Science and Humanities, 2026)
Adolescent gadget use continues to increase along with technological advancements and easier internet access. Gadgets are used for communication, accessing information, social media, entertainment, and learning. According to the APJII survey, internet penetration in Indonesia has reached 79.51%. The high intensity of gadget use is presumed to affect the quality of attachment between parents and adolescents. This study aimed to determine the relationship between the intensity of gadget use and parent–adolescent attachment among students at SMA Negeri 1 Kota Jambi. This quantitative study employed a correlational approach involving 80 students selected using purposive sampling. The intensity of gadget use was measured using a scale developed by the researcher, while attachment was assessed using the Inventory of Parent and Peer Attachment (IPPA). Data were analyzed using SPSS version 25. The results showed a very weak negative and statistically non-significant relationship between the intensity of gadget use and attachment (r = -0.029; p = 0.796), indicating that increased gadget use was not accompanied by a meaningful change in attachment. It was concluded that high gadget use intensity was not a factor associated with lower parent–adolescent attachment. Other factors, such as parenting style, communication, and time spent together with the family, may play a more important role.